Factors related to cardiovascular diseases in adult people served at the PNP. Hospital Augusto B. Legu´ıa - 2017 - Matos Uribe, Fausto Francisco (2023)
Determine factors related to cardiovascular diseases in adults treated at the PNP Augusto B. Leguía Hospital. Rimac-2017. Material and methods: The study was observational, retrospective and analytical, the sample design is simple random, a random sample of 1284 patients and medical records was taken between the months of October to December 2017, multiple binary logistic regression was used to determine the variables (predictors) that are related to cardiovascular diseases, binary qualitative dependent variable that take values 1=has cardiovascular disease, 0=does not have the disease. Results: from a total of 12 predictors (classiﬁed into factors): gender, age, race, body mass index, alcoholism, smoking, physical activity, cholesterol level, triglyceride level, systolic pressure, diastolic pressure, diabetes; The predictors were signiﬁcant at 5 % to predict cardiovascular disease: Age, alcoholism, cholesterol, triglycerides, systolic blood pressure and diastolic blood pressure; the Hosmer-Lemeshow goodness-of-ﬁt test was not signiﬁcant (p¡0.05), which indicates that there is a good ﬁt of the logistic model to the observations; the predictive capa-city of the estimated model to classify the observations correctly was 85.6 %; the area under the ROC curve is 0.92, with a 95 % conﬁdence interval (0.905-0.935), which indicates that the model has discriminant power to correctly classify healthy versus sick with a probability of 92 %. Conclusion: The binary logistic regression proved to be a good method to determine factors that are related to cardiovascular diseases and also make predictions.